Everyday Information Needs and Information Seeking Habits in the Countryside: a Study of a Local Community - Gorazd Vodeb (Knjižnica)
ABSTRACT Purpose: The research attempts to provide an insight into the information world of the Slovenian countryside. It presents the first results of an exploratory study of information needs, information seeking habits and types of information sources. Methodology/approach: Brenda Dervin's Sense-Making Methodology was used as the theoretical basis for this research. 25 open structured interviews with inhabitants of a local community were conducted based on purposive sampling. Interview recordings were transcribed, summarised and analysed using the qualitative content analysis approach. Results: The analysis results in recognizing the types of gaps in the context of an individual, economic activities and in the context of a local community. Gap categories are described with regard to questions or problems and the ways of solving them. There are 20 categories describing gaps in the context of an individual, 17 categories which present economic activities – and 6 categories which pertain to a local community. Findings about information needs and the ways of seeking information stress the key role of information sources in farming and prevalence of interpersonal exchange of information and experts' opinion in the context of individual problem solving. Research limitation: The generalisation of results is not possible due to the sample size. Originality/practical implications: The findings contribute to understanding of information needs and ways of information seeking in the Slovenian countryside.